Two new species of Clathrosperchon (Hydrachnidia: Rhynchohydracaridae), and phylogenetic placement of Rhynchohydracaridae - Batista-ribeiro, Dante; Costa, Samuel Geremias Dos Santos; De Castro, Luiz Alexandre Simoes [UNESP]; Pepato, Almir Rogerio (Systematic & Applied Acarology Soc London, Natural History Museum, 2024)
Two new Clathrosperchon (Rhynchohydracaridae: Hydryphantoidea) species were described (Clathrosperchon nunesae sp. nov. and C. bitucai sp. nov.) and tabular and dichotoumous keys to the known Clathrosperchon species based on adults are provided. In addition, the phylogenetic placement o f Rhynchohydracaridae was inferred using five molecular markers: COI, 18S, 28S, HSP70 and SRP54, testin g previous hypothesis that the family may be more closely related to Neohydrachnidia than Hydryphantoidea due to larval characters. Our results recovered Rhynchohydracaridae nested among Lebertioidea, as sister group to Limnesiidae, and the traditional composition of Hydryphantoidea and Lebertioidea could be rejected based o n AU-test. Given the larval characters and the recovered phylogenetic placement of the family, we propose that Rhynchohydracaridae must be included in Neohydrachnidia. This paper represents the first record o f Hydrachnidia for the Minas Gerais State, Brazil, and is also the largest dataset of neotropical water mite s included in a phylogenetic inference to date.
Keywords: Water mites; Clathrosperchon; Hydryphantoidea; Lebertioidea; phylogenetic placement; integrative taxonomy.